Differential Associations of IL-4 With Hippocampal Subfields in Mild Cognitive Impairment and Alzheimer’s Disease - Boccardi, Virginia; Westman, Eric; Pelini, Luca; Lindberg, Olof; Muehlboeck, J-Sebastian; Simmons, Andrew; Tarducci, Roberto; Floridi, Piero; Chiarini, Pietro; Soininen, Hilkka; Kloszewska, Iwona; Tsolaki, Magda; et al. (Frontiers in Aging Neuroscience, 2019)
Background/Aims: A bi-directional communication between the immune system and the central nervous system has been recently suggested. Among many cytokines, the role of IL-4 - with anti-inflammatory properties- in counteracting age-related inflammatory changes in the brain is strongly supported among studies. With this study, we aimed at investigating the association between volumetric measures of hippocampal subregions -in healthy older controls (HC), subjects affected by mild cognitive impairment (MCI) and Alzheimer’s Disease (AD)- with circulating levels of IL-4. Methods: From AddNeuroMed Project 113 HC, 101 stable MCI (sMCI), 22 converter MCI (cMCI) and 119 AD were included. Hippocampal subfield volumes were analyzed using Freesurfer 6.0.0 on high-resolution sagittal 3D-T1W MP-RAGE acquisitions. Plasmatic IL-4 was measured using ELISA assay. Results: IL-4 was found to be a) positively associate with left subiculum volume (β=0.226, p=0.037) in sMCI and b) negatively associate with left subiculum volume (β=-0.253, p=0.011) and left presubiculum volume (β=-0.257, p=0.011) in AD. Conclusion: Our results indicate a potential neuroprotective effect of IL-4 on the areas of the hippocampus more vulnerable to aging and neurodegeneration.